TIM‐3 expression induces resistance to PD‐1 inhibitor in G‐CSF‐producing lung spindle cell carcinoma: A case report - Fumiko Hayashi; Kazumasa Akagi; Hirokazu Taniguchi; Toyoshi Matsutake; Hiromi Kawahara; Ichiro Sekine; Hiroshi Gyotoku; Shinnosuke Takemoto; Hiroshi Soda; Kazuto Ashizawa; Hiroshi Mukae (Thoracic Cancer, 2023)
Abstract Lung spindle cell carcinoma is an aggressive subtype of pleomorphic lung cancer resistant to cytotoxic chemotherapy. Programmed cell death‐1 (PD‐1) inhibitors have been reported to have clinical effects in patients with spindle cell carcinoma; however, the resistance mechanism to PD‐1 inhibitors is yet to be fully elucidated. Herein, we report the case of an 88‐year‐old man with G‐CSF‐producing spindle cell carcinoma who acquired resistance to PD‐1/PD‐ligand 1 (L1) inhibitor in an early setting after a remarkable response. A histopathological review of the resistant specimen revealed a low count of CD8+ T cells and a predominant presence of M2 and TIM‐3+ macrophages, indicating the presence of an immunosuppressive microenvironment. Our findings suggest a novel resistance mechanism to PD‐1/PD‐L1 inhibitors in G‐CSF‐producing spindle cell carcinoma.